A Survey of Fetal Deaths as Reported to a Medical Examiner's Office. (5th June 2022) - Sandoval, Alicia; Winston, David
Abstract: This article is a review of the fetal deaths reported to the Pima County Office of the Medical Examiner in Tucson, Arizona, from January 2000 to May 2020. The 115 cases included in this study were analyzed for the decedent's estimated gestational age, sex, maternal drug use, toxicology results, and cause of death. The male/female ratio was 0.95:1.0. The average gestational age of nonterm infants older than 20 weeks was 27.2 weeks. Nearly half of the cases had suspected or known maternal drug use. In these cases, cocaine and methamphetamine were most often detected in postmortem testing of the fetus. The most common causes of death in descending frequency were intrauterine fetal demise of unknown etiology, drugs, infection, and prematurity. Other notable causes of death included trauma and placental abruption. Congenital malformations were detected in only 3.5% of cases.